EMP32 is required for the cis-splicing of nad7 intron 2 and seed development in maize - Yang, Yan-Zhuo (RNA Biol, 2020)
Pentatricopeptide repeat (PPR) proteins play an important role in post-transcriptional regulation of mitochondrial gene expression. Functions of many PPR proteins and their roles in plant growth and development remain unknown. Through characterization of an empty pericarp32 (emp32) mutant, we identified the function of Emp32 in mitochondrial intron splicing and seed development in maize. The loss-of-function mutant emp32 shows embryo lethality with severely arrested embryo and endosperm development, and over-expression of Emp32 rescues the embryo-lethality. EMP32 is a P-type PPR protein targeted to mitochondria. Loss of function in Emp32 dramatically decreases the splicing efficiency of nad7 intron 2, while complementation of Emp32 restores the splicing efficiency. Although nad7 intron 2 is partially spliced in the wild type, over-expression of Emp32 does not increase the splicing efficiency. The splicing deficiency of nad7 intron 2 blocks the assembly of mitochondrial complex I and dramatically reduces its activity, which may explain the embryo-lethality in emp32. In addition to the one copy of nad7 in the maize mitochondrial genome, we identified one to six copies of nad7 in the nuclear genomes in different maize inbred lines. These copies appear not to be expressed. Together, our results revealed that the P-type PPR protein EMP32 is required for the cis-splicing of nad7 intron 2 and seed development in maize.